Empowering Fisherwomen and Women of GMIT Siloam Oebelo Kecil Community Through Fish Crackers Making Training - Lumba, Anderias J.F.; Nomleni, Fransina Th.; Rupidara, Anggreini D.N. (Universitas Serang Raya, 2024)
The local potential of Tanah Merah Village is fish and lontar, which are still in the form of caught fish, dried fish, and lontar sugar. The fishermen and women of GMIT Siloam Oebele stated that fish, which is the village's potential, is often not sold out and dries up. Fish processing has not been done much by the existing community, and the sales are mostly done in traditional markets. Through the steering committee of Artha Wacana Christian University, community service activities with partners are intended to be members of local potential for learning and mentoring innovations for partners. The objectives of this program are: 1). Transfer of knowledge of fish cracker processing innovations from local ingredients, 2). Creativity to improve branding and marketing system to UKAW partners, 3). Adding soft skills and hard skills outside the classroom, 4). Increase cooperation between Artha Wacana Christian University partner’s. The method applied to service activities is adult learning through counseling and empowerment and in producing fish crackers. The method applied in the service activity is adult learning through counselling, empowerment, and assistance in producing fish crackers. The activity stages began with the SC Service Team conducting a survey of potential resources at the location, designing utilisation activities, training and mentoring in product creation, packaging, and marketing in a simple manner for UKAW partner businesses. The result of this activity is that the fisherwomen and Women of the GMIT Siloam community have the ability to make fish cracker products and packaging that can be marketed online as a product that can improve the community's economy. Products were judged to have excellent taste, color, and shape, and participants were satisfied with the activities. Sustainability of activities with UKAW and partners can be done through other programmes such as preventing the disposal of damaged fish into the environment and training in simple bookkeeping.